Common challenges of online learning during the COVID-19 pandemic - Nkwanyana, Nokulunga Nokwethemba; Fagbadebo, Omololu (Edelweiss Applied Science and Technology, 2025)
The advent of the COVID-19 pandemic has not only led to devastated economies but has also affected education systems globally. The unpredictability of this pandemic and its restrictions have necessitated the adoption of a multi-modal approach involving both contact and online learning platforms by Higher Education Institutions. Thus, due to the COVID-19 pandemic, educational institutions shifted to online learning platforms. The study employed qualitative methodology within a case study design. Data was collected using pure qualitative semi-structured interviews with open-ended questions. The researchers interviewed selected students and lecturers from the ML Sultan Campus of the Durban University of Technology. The study employed a purposive sampling technique under the non-probability method. The findings of this study indicate that the implementation of the tools used for online learning and teaching during the COVID-19 pandemic has been scattered across different platforms. An exciting finding was demonstrated by a high percentage of the selected participants among the DUT staff members and students who showed a wavering response, somewhat agreeing that although the tools used for online learning and teaching during the COVID-19 pandemic have impacted lives, they successfully assisted both the lecturers and students. The study results revealed that the most popular tools used by learners throughout the pandemic were Microsoft Teams, Modular Objective-Oriented Dynamic Learning Environment (Moodle), Queens, Zoom, and Learn Wise. The thematic analysis method was used to analyze data using Nvivo. The data captured from both sessions (interviews and focus group discussions) were deductively coded using software (Nvivo version 12). In this process, the transcribed interview data were divided into different meaningful codes. The codes were developed based on the differences, similarities, and meanings from the transcribed data. This process allows the researcher to fine-tune data into convenient themes and subthemes. During the analysis phase, information gathered from structured interviews was verbatim transcribed, and pertinent quotes from this data were used to support the discussion on themes. The study does not disclose the identities of the main informants to protect their anonymity.